Sistem Monitoring Kualitas Udara di Ruangan Tertutup Berbasis IoT Menggunakan Sensor MQ-135 dan GP2Y1014AU0F - Sujiarta, Ardi; Wedashwara W, I Gede Putu Wirarama; Zubaidi, Ariyan (Journal of Computer Science and Informatics Engineering (J-Cosine), 2023)
Air quality is now decreasing, mainly in urban areas and industrial centers. Decreasing air quality can occur indoors, especially in a closed room such as a kitchen room. Conditions like this will certainly be very detrimental because it can interfere with health, disturbing comfort and can damage property. In this study, a system was made to monitor air quality, especially in closed rooms by utilizing IoT technology using MQ-135 and GP2Y1014AU0F sensors. Based on tests conducted in the kitchen room, when cooking the gas status was in the medium category and the dust status was in the good category, whereas after cooking the gas and dust status were in the good category. Then in the warehouse room, the gas status is in the medium category and the dust status is in the unhealthy category. Based on the test results, the system built has been running well and is possible to be implemented.